Vanessa O'Hanlon. - O'Hanlon, Vanessa (Melbourne, Victoria : Australian Broadcasting Corporation, 2012)
"As the National Weather Presenter on ABC News Breakfast and ABC News 24 Vanessa has reported on some of Australia and the world's most significant weather events... ...Away from the camera or microphone Vanessa has an insatiable sense of adventure, travel and photography. She regularly contributes to Tour The World and The Home Journal. Vanessa is the sole writer and photographer of her own travel blog, Travelazzi."
Title from title screen (viewed on 24 March 2016)
Mode of access: Available online. Address as at 04/04/2016
Selected for archiving
Keywords: O'Hanlon, Vanessa; Travelers' writings, Australian; Weather forecasting -- Australia; Australian